1989
DOI: 10.1164/ajrccm/139.5.1139
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of the Bronchial Mucosa to99mTc-DTPA in Asthma

Abstract: Previous investigators, using 99mTc-DTPA aerosol as a marker to assess epithelial permeability in asthma, did not find an increased permeability in this group. However, they either failed to deliver the aerosol to the optimal site (bronchial mucosa, not alveoli) or failed to account for mucociliary clearance in analyzing their results. We studied 10 asthmatics and eight age-matched control subjects using a dosimeter (Spira-Elektra 2) and a carefully controlled breathing pattern to deliver aerosol to the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 7 publications
1
52
0
1
Order By: Relevance
“…5) Clearance during data acquisition could contribute to the reduction in the apparent difference in PI between aerosols of different tonicities. Over the period of time in our experiments, about 10-20% of the radioactivity would be expected to be cleared from the central and peripheral regions, both in normal and in asthmatic subjects [35,36]. Mucociliary clearance (MCC) was shown to be faster after nonisotonic aerosols [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…5) Clearance during data acquisition could contribute to the reduction in the apparent difference in PI between aerosols of different tonicities. Over the period of time in our experiments, about 10-20% of the radioactivity would be expected to be cleared from the central and peripheral regions, both in normal and in asthmatic subjects [35,36]. Mucociliary clearance (MCC) was shown to be faster after nonisotonic aerosols [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Airway mucosal permeability is increased in smokers with normal lung function and in asthmatic patients who do not smoke. 99,100 Another proposed mechanism of corticosteroid resistance is the down-regulation of ß 2 -adrenergic receptors in lymphocytes that is caused by cigarette smoking. 101 Changes in levels of cytokines and inflammatory mediators may also play a role.…”
Section: Mechanisms Of Corticosteroid Resistancementioning
confidence: 99%
“…Because of this feature, the lung retention ratio depends mainly on the permeability in the peripheral lung, where the mucociliary transport takes place very slowly [19]. Previous reports have demonstrated that airway permeability is increased in unstable asthmatics [20] and COPD patients [21], but not in stable asthmatics [22]. In the present study, the retention ratio of the right peripheral lung at 60 min after inhalation was significantly lower in COPD patients than in normals, suggesting that the epithelial permeability of the small airways and alveoli may be increased in COPD subjects.…”
Section: Discussionmentioning
confidence: 99%